Approaching MALDI molecular imaging for clinical proteomic research: current state and fields of application. (December 2010) - Rauser, Sandra; Deininger, Sören-Oliver; Suckau, Detlev; Höfler, Heinz; Walch, Axel
MALDI imaging mass spectrometry ('MALDI imaging') is an increasingly recognized technique for biomarker research. After years of method development in the scientific community, the technique is now increasingly applied in clinical research. In this article, we discuss the use of MALDI imaging in clinical proteomics and put it in context with classical proteomics techniques. We also highlight a number of upcoming challenges for personalized medicine, development of targeted therapies and diagnostic molecular pathology where MALDI imaging could help.